Comparison of Old-age Pension Policy in China and Russia: the Common and the Specific - Tianhong Chen (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
In the process of transforming from planned economy to market economy, both China and Russia faced the issue of pension reform. There are similarities in the reform and development process and the system model of the pension security system in China and Russia. Transition from planned economy to market economy and aggravation of population aging are main reasons for the reform of pension system in both countries. Under the influence of the World Bank and other international organizations, China and Russia have gradually established a multi-tier pension system, with the state, enterprises and individuals sharing the pension costs. Differences also exist in the old-age security system of China and Russia.